2020
DOI: 10.3389/fonc.2020.01108
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA MNX1-AS1 Promotes Progression of Triple Negative Breast Cancer by Enhancing Phosphorylation of Stat3

Abstract: Triple negative breast cancer (TNBC) accounts for less than a quarter of breast cancer but has the poorest survival outcome and is prone to relapse as well as metastasis due to its aggressiveness and lack of therapeutic target. Herein, we analyzed the TCGA datasets of lncRNA expressional profiles of breast cancer vs. normal tissue and TNBC vs. Non-TNBC subtypes and screened a long non-coding RNA (lncRNA) MNX1-AS1 overexpressing in TNBC. We found that MNX1-AS1 were upregulated in TNBC tumor tissues and correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…et al. found that the MNX1-AS1 lncRNA was able to enhance STAT3 phosphorylation, thereby driving TNBC progression ( 24 ). ADAMTS9-AS2 has also previously been shown to suppress lung and ovarian cancer growth ( 17 , 19 ), but its functional role in TNBC has not been previously clarified.…”
Section: Discussionmentioning
confidence: 99%
“…et al. found that the MNX1-AS1 lncRNA was able to enhance STAT3 phosphorylation, thereby driving TNBC progression ( 24 ). ADAMTS9-AS2 has also previously been shown to suppress lung and ovarian cancer growth ( 17 , 19 ), but its functional role in TNBC has not been previously clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In this step, we deleted four articles since they provided unavailable data [ 40 ] or data from TCGA or CEO [ 12 , 26 , 27 ]. Finally, 10 articles were chosen for this meta-analysis [ 12 , 15 , 17–19 , 22 , 23 , 27–29 ]. The flow diagram of study search and selection is summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer, Cheng et al [ 16 ] first proposed MNX1-AS1 acted as a functional oncogene that could induce the epithelial-mesenchymal transition of cancer cells via activation of AKT/mTOR signaling pathway and upregulation of its natural sense transcript MNX1. Besides, a most recent study revealed MNX1-AS1 could enhance the aggressiveness of triple-negative breast cancer cells through interacting with Stat3 and increasing its phosphorylation in a p-JAK-dependent manner [ 17 ]. In prostate cancer, MNX1-AS1 was proved to facilitate cancer cell proliferation, migration, and invasion, but its molecular mechanisms remain unknown [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating reports have revealed that lncRNAs act as tumor facilitators and suppressors, thereby affecting the development of tumors [8,9]. For example, long non-coding RNA MNX1-AS1 promotes TNBC development by enhancing phosphorylation of Stat3 [10]. PCAT6 promotes TNBC cell proliferation, migration, invasion, and EMT [11].…”
Section: Introductionmentioning
confidence: 99%